Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Dan Loyalitas Pelanggan - Ancela Siarmasa; Cynthia Imelda Tjokro; Saul Ronad Jacob Saleky; Stevanus Gomies; Victorio Fernando Nahuway (P3M Politeknik Negeri Ambon, 2023)
This research is empirical research, which aims to analyze the influence of service quality on consumer satisfaction and customer loyalty. The population of this research is all Wayame supermarket customers. The sampling technique used accidental sampling, where the number was determined using the Slovin formula and the sample size was 145 respondents. The analysis technique used is multiple linear regression analysis, where the hypothesis test uses the t-statistical test to test the partial regression coefficient with the degree of significance used being 0.05 or 5%. The results of research on 145 respondents gave the research conclusion that service quality has a positive effect on consumer satisfaction and customer loyalty. This is proven by the coefficient of determination obtained in this study of 0.969, 0.959 and 0.234 or around 89.6%, 95.9% and 23.4%. This means that the influence of the independent variable (service quality) on the dependent variable (consumer satisfaction) is 89.6%, the influence of the service quality variable on loyalty is 95.9% and the influence of the consumer satisfaction variable on customer loyalty is 23.4%. % while the remaining 10.4%, 4.1% and 76.6% are influenced by other variables. Based on these results, it can be concluded that Service Quality has a positive influence on customer satisfaction and customer loyalty, and customer satisfaction has a positive influence on customer loyalty.Keyword: Service Quality, Customer Satisfaction, Customer Loyalty